Understanding Brand Equity Dynamics: The Role of Value Co-Creation in the Development of a Brand Equity Model for the Fashion Industry - Riffat Zulfiqar; Ashfaq Ahmad Mirza (Social Science Review Archives, 2025)
This research study intends to analyze the impact of value co-creation on customer-based brand equity. Specifically, it measures co-creation across four dimensions: the first four factors are willingness to cooperate, perceived adaptability, willingness to engage, and customer involvement. Mediating variables include behavioral outcomes (Product satisfaction, word of mouth, loyalty, and brand engagement) along with experiential outcomes (sensory, affective, intellectual, and behavioral responses). A convenience sampling method is employed in data collection through questionnaires from a sample population of active fashion consumers who exhibit interest and purchasing behavior toward various fashion brands. The data have been analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM). Value co-creation enhances the Customer-based Brand Equity (CBBE) of the fashion industry in context of customer’s satisfaction, customer loyalty, and positive word of mouth. It offers practical insights into how fashion firms may improve their business models by incorporating direct customer feedback, making items more relevant and adaptable to shifting preferences. Fashion brands can positively distinguish themselves in this competitive world by applying co-creation strategies. It emphasizes the changing role of customers in the fashion industry, from passive receivers to active co-creators, and the transition toward more customer-centric business structures.